Super Rice With High Sink Activities Has Superior Adaptability to Low Filling Stage Temperature - Xu, Congshan; Yang, Fei; Tang, Xinao; Lu, Bo; Li, Ziyu; Liu, Zhenghui; Ding, Yanfeng; Ding, Chao; Li, Ganghua (Frontiers in Plant Science, 2021)
To investigate the differential responses of super rice grain filling to low filling stage temperature (LT) and the regulative effect of nitrogen panicle fertilizer (NPF), physiological and molecular experiments were conducted with two super rice varieties (N7 and N9108), two different filling stage temperature treatments implemented by applying two sowing dates (CK: May 30th, Tmean=24.7oC and LT: July 1st, Tmean=20.3oC), and two NPF level (0 and 150 kg ha-1). In this study, LT, NPF and simultaneous LT and NPF treatments suppressed the grain filling in all varieties with different level. Under LT or NPF treatments, the reduction of grain weight, seed setting rate and filling rate were closely associated with suppressed starch biosynthesis rate in inferior seeds, suggesting that reduced starch biosynthesis rate and related genes expression (FLO4、SBE and PHO1) was responsible for the grain filling reduction. Under LT or NPF treatments, significant higher grain filling rate and lower variance were found in N9108 compared to that in N7, which were closely related to their higher starch biosynthesis ability and related genes expression. These results raise a possibility that super rice with higher sink activities has superior adaptability to LT and NPF due to their higher sink activities.